A formulação e a resolução de problemas nos primeiros anos do ensino fundamental - Mendonça, James Madson (2017)
This present research intended to answer the questioning: which are the theoretical and practical knowledge that base the formulation and resolution of problems that Mathematic teachers of the early years of Elementary School need to develop an alternative pedagogical practice, capable and different of that which endures in the school context? To answer this question it was elaborated an objective which had as parameters, study, identify, analyze and systematize the essential theoretical and practical knowledge which refers to the formulation and resolution of problems which could, somehow, contribute with the improvement of the Mathematic teaching actions practiced by the teachers of the early years of Elementary School. It was developed a bibliographic research to search alternative answers, emphasizing, therefore, the resolutions of problems as one of the methodological and innovative education proposes, which enhance the teaching-learning process breaking with the current reproductive and repetitiveimitative actions to contextualized actions which stimulate the participation of the student, in or out the classroom, in a playful way some mathematics scholar contents or formal like the ones of daily life too. To enable these innovative teaching proposals, the continuous training of the teacher must be a constant in the school life and not just sometimes as it was sufficient for the development of the education in Brazil. Therefore, the learning proposal which oriented the theoretical and methodological bases of this work was The Cognitive Theory of Bruner, which is associated to the conceptions of problems and not to mathematics exercises evidenced by the stamp of the cognitive development of the child, where she could learn any subject, in any age, in any stage of development, been respected, however, her way of thinking, by the teachers. In addition, the trend in mathematics education become hopeful to search fields committed with studies as the problems resolutions, where everyone, in a general terms, as well as teachers, students and professionals of this area can make mathematics in many ways and in different expressiveness, representing, therefore, the curricular contents of the current levels of education.